Dynamics of Academic Stress, Emotional Intelligence, and Behavioral Transformation Among Students: A Case Study at Ponpes Zainul Hafidz, Darul Qur’an Walhadis, and Insan Budi Mulia - Utama, Zoli (ISLAMIKA, 2026)
This study is motivated by the limited research on the interaction between academic stress, emotional intelligence, and behavioral transformation among students in Indonesia pesantren, despite its significant impact on students’ academic performance, mental resilience, and social adaptation. The study aims to explore the forms and sources of academic stress, examine the role of emotional intelligence as a coping mechanism, and analyze how these factors interact to shape adaptive and maladaptive behaviors among santri. The research adopts a qualitative case study design, involving three Islamic boarding schools: Zainul Hafidz, Darul Qur’an Walhadis, and Insan Budi Mulia with a purposive sample of students selected for interviews and observations. Data were collected through in-depth interviews, participant observations, and field notes, and analyzed using thematic and comparative analysis techniques. The findings reveal that academic stress primarily arises from memorization demands, cognitive difficulties in understanding classical texts, and social-environmental pressures. Emotional intelligence functions as a critical buffer, enabling students to regulate emotions, manage study schedules, and engage proactively with teachers and peers. Moderating factors, including teacher mentorship, peer support, family expectations, and institutional schedules, significantly influence behavioral outcomes. The study concludes that adaptive behaviors emerge when students possess strong emotional intelligence and receive supportive institutional and social environments, while maladaptive behaviors occur under low emotional regulation or high unmitigated stress. The implications include advancing theoretical understanding of stress-emotion-behavior dynamics in pesantren and informing practical strategies for educational stakeholders to enhance students’ emotional resilience and engagement, with future research suggested in more schools using mixed methods.